Association Between Physical Activity and Sleep in Adults With Chronic Pain: A Momentary, Within-Person Perspective. Issue 4 (1st April 2014) - Andrews, Nicole E.; Strong, Jenny; Meredith, Pamela J.; D'Arrigo, Rachel G.
Abstract : Background: Individuals with chronic pain consider improved sleep to be one of the most important outcomes of treatment. Physical activity has been shown to have beneficial effects on sleep in the general population. Despite these findings, the physical activity–sleep relationship has not been directly examined in a sample of people with chronic pain. Objective: This study aimed to examine the association between objective daytime physical activity and subsequent objective sleep for individuals with chronic pain while controlling for pain and psychosocial variables. Design: An observational, prospective, within-person study design was used. Methods: A clinical sample of 50 adults with chronic pain was recruited. Participation involved completing a demographic questionnaire followed by 5 days of data collection. Over this period, participants wore a triaxial accelerometer to monitor their daytime activity and sleep. Participants also carried a handheld computer that administered a questionnaire measuring pain, mood, catastrophizing, and stress 6 times throughout the day. Results: The results demonstrated that higher fluctuations in daytime activity significantly predicted shorter sleep duration. Furthermore, higher mean daytime activity levels and a greater number of pain sites contributed significantly to the prediction of longer periods of wakefulness at night. Limitations: The small sample size used in this study limits the generalizability of the findings. Missing data may have led to overestimations or underestimations of effect sizes, and additional factors that may be associated with sleep (eg, medication usage, environmental factors) were not measured. Conclusions: The results of this study suggest that engagement in high-intensity activity and high fluctuations in activity are associated with poorer sleep at night; hence, activity modulation may be a key treatment strategy to address sleep complaints in individuals with chronic pain.